The Effect Of Various Compatibilizers On Properties Of Mengkuang Leaf Fibre Filled Poly (Lactic Acid) Composite - Ibrahim, Nur Fatin Nabila (Universiti Sains Malaysia, 2018)
Poly (lactic acid)/mengkuang leaves fibres (PLA/MLF) polymer composites were prepared by melt compounding technique. Ethylene methyl acrylate-glycidyl methacrylate (EMA-GMA) and styrene butadiene butylene styrene grafted maleic anhydride (SEBS-g-MA) were used as compatibilizers in PLA/MLF composites to enhance the properties of the composites. In the first stage, the study focused on the contribution of different compositions (10, 20, 30, and 40 wt. %) of MLF in PLA. The evaluation was performed through tensile test, thermal analysis by differential scanning calorimetry (DSC), morphological analysis by scanning electron microscope (SEM), and chemical interaction study by fourier transform infrared (FTIR) testing. The percentage elongation, modulus, and tensile strength of PLA/MLF composites decreased significantly in comparison with pure PLA. Degree of crystallinity of PLA/MLF composite slightly reduced with the incorporation of MLF. Based on the DSC thermogram, PLA/MLF composites show the presence of bimodal melting peaks due to melt-recrystallization mechanism that might happen during heating. SEM observation indicated poor interaction between components and poor dispersion of the filler. In the second stage, EMA-GMA was introduced to improve the properties of PLA/MLF composites. However, similar trend of reduction in mechanical strength was observed, suggesting that EMA-GMA could not act as a good compatibilizer in PLA/MLF composites. Degree of crystallinity of PLA/MLF reduced in the presence of EMA-GMA. Fracture surface also observed to have agglomeration. In the third stage, SEBS-g-MA was introduced as a compatibilizer. The presence of SEBS-g-MA also could not improve tensile properties of the composite. However, better properties were observed in the system with EMA-GMA compared with SEBS-g-MA.